Mechanical properties of FDM 3D printed component using self-made PLA-titanium filament: hardness perspective - Mahros Darsin; Faris Ahmad Junaedi; Agus Triono; Yuni Hermawan; Intan Hardiatama; R. Koekoeh Koenjtoro Wibowo; Hari Arbiantara Basuki (Jurnal Polimesin, 2024)
3D printing, also known as additive layer manufacturing, is a technique that creates three-dimensional objects or any shape from a digital model. It works by building objects layer-by-layer, similar to how a laser printer operates. Fused Deposition Modeling (FDM) is a widely used technique in 3D printing because it is easy to use, cost-effective in production, and environmentally friendly. This study focuses on a self-made filament made of a PLA-titanium mixture. PLA is a biodegradable thermoplastic polymer sourced from plants, whereas titanium is a strong, lightweight, and corrosion-resistant metal. To measure the hardness of different materials, there are several methods available. In this study, the Shore D hardness test, specifically designed for polymer materials, was used. Data were collected using the Taguchi method, specifically L4 (23), and the data were analysedusingAnalysis of Variance (ANOVA). The variations in print parameters examined in this study include nozzle temperature (230°C and 240°C), layer height (0.2 mm and 0.3 mm), and print speed (30 mm/s and 40 mm/s). The aim of this study was to determine whether there were any changes in the hardness of the specimens. The ANOVA results revealed that the most influential parameter was print speed, with a contribution value of 56.01%. The results demonstrated that the printing parameters affected the hardness of the printed specimens. The highest hardness level of 56.3 Shore D was obtained with a nozzle temperature of 240°C, a layer height of 0.3 mm, and a print speed of 30 mm/s. The application of this study was demonstrated through the creation of dentures made from PLA-titanium.